Caregiver burden, work-family conflict, family-work conflict, and mental health of caregivers: A mediational longitudinal study - Kayaalp, Alper; Page, Kyle J.; Rospenda, Kathleen M. (Work and stress, 2021)
Caregivers are responsible for the care of another, such as a young adult, disabled child, elderly parent, or sick spouse. Individuals who have caregiving responsibilities must blend the often-contradictory behavioural expectations from the different roles in which they reside. Building on the theoretical foundations of Conservation of Resources theory, this study tests a mediational model explicating the process through which caregiver burden impacts mental health through work-family conflict among a community sample of 1,007 unpaid caregivers in the greater Chicago area who responded to a mail survey at three time points. Structural equation modelling analyses indicate strain-based conflict as being a consistent mediator between caregiver burden and mental health at baseline and two years later. These findings can inform practice and policy for workers with caregiving responsibilities.